Aktualisasi Konsep Good Governance Dalam Mengantisipasi Masalah Ketenagakerjaan Sebagai Salah Satu Tantangan Pembangunan - Daradjat, Adjat (Jurnal Administrasi Bisnis, 2010)
The concept of good governance is one of the current paradigm of development inpublic sector that enables to overcome development problems and enables to motivatethe acceleration in achieving the objectives more quickly. This matter particularlyrefers to the rise of development challenges, which must be faced by the state and itsgovernment. It relates to internal demands in terms of the fulfillment of society needs,service improvement, problems handling and solving, and also global challenge interms of the increase of competitive ability.The above-mentioned concept implies that there is a shift of paradigm and con-cept in the state role to fulfill the needs and service to the society from the welfarestate, which gives greater role to the state in fulfilling all the main needs to its citizensthat is burdening and stressing as it creates inefficiency and uneconomical.The concept of good governance implies paradigm that government matters,especially in fulfilling public needs, must be handled together with other domains oflife beside government, namely: domain of entrepreneurs and domain of society.In terms of manpower sector in Indonesia, the concept of good governance hasbeen stipulated as the policy in various matters, such as in expanding employmentand job opportunities, in improving the quality of manpower, in industrial relationsphenomena, and in protecting manpower.This matter is conceptually influenced by the failure in determining the devel-opment choices, particularly the model choices in implementing state administrationin terms of economic, technology and politic. Therefore, development model thatis oriented to human resource is considered to be the most appropriate model inimplementing the concept and the policy of good governance.Keywords: good governance, public services, welfare state